Sn and Ti influences on intermetallic phases damage in hot dip galvanizing - V. Di Cocco (Fracture and Structural Integrity)
Protection against metallic materials corrosion is one of the most important means to reduce both maintenance costs and environmental impact. In the last years new studies on chemical baths compositions and fluxes have been performed in order to improve processes, corrosion resistance and mechanical behavior of Zn based coatings. Chemical bath composition is often improved by the Sn addition which increases the fluidity of the melt. Ti addition makes the coatings to change color under appropriate heat treatment. In this work a comparative microstructural analysis, in Zn-Sn and Zn-Ti coatings, is performed to evaluate intermetallic phases formation kinetics and the influence of intermetallic microstructure on coating damage under constant bending deformation.